Frequency of CHEK2*1100delC in New York breast cancer cases and controls - Robson Mark; Satagopan Jaya; Huang Helen; Yossepowitch Orit; Johnson Steven; Gregersen Peter; Rapaport Beth; Kolachana Prema; Kirchhoff Tomas; Pierce Heather; Offit Kenneth; Scheuer Lauren; et al. (BMC, 2003)
Abstract Background The 1100delC CHEK2 allele has been associated with a 1.4-4.7 fold increased risk for breast cancer in women carrying this mutation. While the frequency of 1100delC was 1.1-1.4% in healthy Finnish controls, the frequency of this allele in a North American control population and in North American breast cancer kindreds remains unclear. Methods We genotyped 1665 healthy New York volunteers and 300 cases of breast cancer for the CHEK2*1100delC. Results The overall frequency of the 1100delC was 3/300 (1.0%) among all cases with either a family history of breast cancer (n = 192) or a personal history of breast cancer (n = 108, of which 46 were bilateral, 46 unilateral, and 16 were male breast cancer cases), compared to a frequency of 5/1665 (0.3%) in healthy controls (p = 0.1). There was no difference in allele frequency among Ashkenazi and non-Ashkenazi controls. Conclusion The relatively low breast cancer penetrance of this allele, along with the low population frequency, will limit the clinical applicability of germline testing for CHEK2*1100delC in North American kindreds.